INTER-SPOUSE COMMUNICATION AND ACCEPTANCE OF FAMILY PLANNING - Rasheed, Nazish; Khan, Zulfia; Khalique, Najam; Siddiqui, Abdul Razzaque; Hakim, Seema (Indian Journal of Community Health, 2011)
Context: Inter-spouse communication majorly influences the decision making process of couples for adopting family planning measures. This factor is especially important in male dominated cultures, where, it is thought unnecessary for men to discuss family planning as child bearing and contraception are presumed to be female matters. Aims: The present study was conducted with the aim to know the extent of inter spouse communication among couples and its impact on use of family planning measures and family size. Settings and Design: The study was conducted among ever married women in the reproductive age group of 15-49 years (n=718) residing in Aligarh, Uttar Pradesh, India. The study was a community based cross-sectional study. Methods and Material: A community based household survey was conducted in the registered areas of urban and rural health training centres of Department of Community Medicine, Jawaharlal Nehru Medical College, Aligarh,Uttar Pradesh. Participants were enquired on various parameters related to their conversations on family planning with their husband, ever use of contraception and their family size. Statistical analysis used: Chi square was applied to test the association. Results: A sizeable portion (18.1%) of women had never conversed with their husbands on family planning matters. Communicators were observed to have lesser number of living children (p<0.001). Current use of contraceptives was significantly associated with inter spouse discussion (p<0.05). 43% women from the study sample had never discussed the choice of a contraceptive method with their husbands. Conclusions: Husband-wife communication plays an important role in family planning acceptance as well as in deciding the final family size.